Overweight and obesity among women at reproductive age in Cambodia: Data analysis of Cambodia Demographic and Health Survey 2014. - Samnang Um; An Yom; Jonathan A Muir; Heng Sopheab (Public Library of Science (PLoS), 2023)
Overweight and obesity increase the risk of cardiovascular disease, type 2 diabetes mellitus, hypertension, stroke, and some type of cancers, and maternal health globally. In Cambodia, the prevalence of overweight and obesity among women aged 15-49 years increased from 6% in 2000 to 18% in 2014, becoming a public health burden. We examined socio-demographic and behavioral factors associated with overweight and/or obesity among women of reproductive age (WRA) in Cambodia. We analyzed data from the 2014 Cambodia Demographic and Health Survey (CDHS) that used a two-stage stratified cluster sampling design. Data analysis was restricted to non-pregnant women, resulting in an analytic sample of 10,818 women. Multivariable logistic regressions were performed using STATA V16 to examine factors associated with overweight and obesity. Prevalence of overweight and obesity among non-pregnant women of reproductive age were 15.2% and 2.8% respectively. Factors independently associated with increased odds of overweight and/or obesity including women aged 20-29 years with adjusted odds ratio [AOR = 2.4; 95% CI: 1.6-3.6], 30-39 years [AOR = 4.6; 95% CI: 3.0-6.9], and 40-49 years [AOR = 6.6; 95% CI: 4.3-10.1], married women [AOR = 1.8; 95% CI: 1.3-2.7], urban residence [AOR = 1.3; 95% CI: 1.1-1.5], and women having at least 4 children [AOR = 1.7; 95% CI: 1.2-2.5]. The factors were associated with decreased odds of overweight and obesity: completed at least secondary education [AOR = 0.7; 95% CI: 0.6-0.8], agricultural work [AOR = 0.7; 95% CI: 0.5-0.8], and manual labor work [AOR = 0.7; 95% CI: 0.6-0.9]. Increased age, married women, living in urban residence, and having at least four children were the main risk factors associated with overweight and/or obesity. Conversely, higher education, working in agriculture, and working in manual labor were negatively associated with overweight and/or obesity. Cambodia's non-communicable disease (NCD) public health programs should consider these characteristic for targeting interventions to further reduce overweight and/or obesity in the coming years.